Africa can claim the 21st century - Nwankwo, Sonny; Rugimbana, Robert (Bradford, England : Emerald Group Pub., 2003)
Can Africa Claim the 21st Century? This was the title of a World Bank report (World Bank, 2000) issued to mark the beginning of the new millennium. The report provided an assessment of sub-Saharan Africa's prospects for economic and social development in the twenty-first century.
Abstracts & keywords; Introduction; On the internal drivers of export performance among Nigerian firms; Exploring the potentialities of export processing free zones (EPZs) for economic development in Africa; The effects of normative social belief systems and customer satisfaction on rural savings programs in Ghana; Cultural orientation: its relationship with market orientation, innovation and organisational performance; The structural adjustment programme and marketing in the manufacturing industry in Nigeria; Leadership lessons from the African tree.
Includes bibliographical references.
Print version record.
Keywords: Management -- Africa; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; Africa -- History; History